Tricuspid annular displacement measured by 2-dimensional speckle tracking echocardiography for predicting right ventricular function in pulmonary hypertension: A new approach to evaluating right ventricle dysfunction. Issue 30 (July 2018) - Li, Yidan; Wang, Yidan; Yang, Yuanhua; Liu, Mingxi; Meng, Xiangli; Shi, Yanping; Zhu, Weiwei; Lu, Xiuzhang
Abstract : Abstract: This study aimed to determine the ability of tricuspid annular displacement measured by 2-dimensional speckle tracking echocardiography (STE) to predict right ventricular (RV) dysfunction in pulmonary hypertension (PH) patients. Here, we present a new method for assessing RV function that also employs STE and is based on measurement of tricuspid annular displacement. A total of 225 patients were divided into 2 groups according to the pulmonary artery systolic blood pressure (PASP), estimated by echocardiographic measurement of tricuspid regurgitation: group I (PASP ≥50 mm Hg) and group II (36 mm Hg ⩽ PASP <50 mm Hg). The tricuspid annular plane systolic excursion (TAPSE), RV index of myocardial performance (RIMP), RV fractional area change (RVFAC), tissue Doppler-derived tricuspid lateral annular systolic velocity (s′), and the tricuspid annular longitudinal displacement (TMAD) parameters were measured. Thirty patients underwent cardiac magnetic resonance (CMR) examination, and right ventricular ejection fraction (RVEF) was calculated. The conventional parameters as well as the TMAD parameters differed significantly between the 2 groups (all P  < .01). Good correlation was observed between the TMAD parameters and CMR-derived RVEF (all P  < .01). The TMAD parameters had moderate predictive value for predicting RV dysfunction in PH patients (all P  < .01). From receiver operating characteristic curves, we determined the optimal cut-off values for TMAD parameters for detecting RV dysfunction with good sensitivity and specificity. The TMAD parameters can predict the decline of RV function in patients with PH and thus provide new diagnostic indices for clinical management of these patients. Abstract : Supplemental Digital Content is available in the text